Immediate Implant Placement: Current Concepts - Dhami, Bhageshwar; Shrestha, Priti; Gupta, Sujaya; Pandey, Nashib (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Immediate implants following extraction has become an increasingly popular strategy to preserve bone and reduce treatment duration. This technique also improves aesthetics by preserving the soft tissues. Immediate implant placement is technically challenging and should only be undertaken by clinicians with considerable experience in implant dentistry, both surgically and prosthetically. The purpose of this article is to provide a general review about immediate implant placements and to summarise various aspects in which this technique can be indicated.